Decision-Making Involvement, Self-Efficacy, and Transition Readiness in Youth With Sickle Cell Disease. Issue 1 (January 2022) - Varty, Maureen; Speller-Brown, Barbara; Wakefield, Bonnie J.; Ravert, Russell D.; Kelly, Katherine Patterson; Popejoy, Lori L.
Abstract : Background: Transition to adult healthcare is a critical time for adolescents and young adults (AYAs) with sickle cell disease, and preparation for transition is important to reducing morbidity and mortality risks associated with transition. Objective: We explored the relationships between decision-making involvement, self-efficacy, healthcare responsibility, and overall transition readiness in AYAs with sickle cell disease prior to transition. Methods: This cross-sectional, correlational study was conducted with 50 family caregivers–AYAs dyads receiving care from a large comprehensive sickle cell clinic between October 2019 and February 2020. Participants completed the Decision-Making Involvement Scale, the Sickle Cell Self-Efficacy Scale, and the Readiness to Transition Questionnaire. Multiple linear regression was used to assess the relationships between decision-making involvement, self-efficacy, healthcare responsibility, and overall transition readiness in AYAs with sickle cell disease prior to transition to adult healthcare. Results: Whereas higher levels of expressive behaviors, such as sharing opinions and ideas in decision-making, were associated with higher levels of AYA healthcare responsibility, those behaviors were inversely associated with feelings of overall transition readiness. Self-efficacy was positively associated with overall transition readiness but inversely related to AYA healthcare responsibility. Parent involvement was negatively associated with AYA healthcare responsibility and overall transition readiness. Discussion: While increasing AYAs' decision-making involvement may improve AYAs' healthcare responsibility, it may not reduce barriers of feeling unprepared for the transition to adult healthcare. Facilitating active AYA involvement in decision-making regarding disease management, increasing self-efficacy, and safely reducing parent involvement may positively influence their confidence and capacity for self-management.